PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA REALITA DI KELAS II SDN 09 PENABAHAN - Ningsih, Sri Utami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem of this research is how to using the media reality in the weight measurement of learning can improve student learning outcomes second grade at elementary school 09 Penabahan District of Sanggau Ledo?". This research to describe the learning outcome of students in the learning weight measurement using the media reality in Class II SDN 09 Penabahan District of Sanggau. The method use descriptive methods with classroom action research. The subject is the second grade students of State Elementary School 09 Panabahan, instrument used IPKG one and two. Analysis of the data for the first and second sub-problems using the formula average and sub Problem 3 using the formula percentage. The data source is a second grade students and teachers (researcher). Research procedure includes planning, action, observation and reflection. The results in the first cycle the average value in the classical 67 or classical learning completeness 55% and the second cycle the average value in the classical 78.05 and classical learning completeness 100%. Concluded that by using the media reality in the weight measurement of learning can improve student learning outcomes second grade elementary school 09 Penabuhan District of Sanggau Ledo. Keywords: using media reality, the value or learning